Stages of plumage maturation of the Tawny-bellied Seedeater: Evidence of delayed plumage maturation and cryptic differentiation between juveniles and females - Facchinetti, Carolina (2011)
In some sexually dichromatic passerines, juvenile males retain a plumage similar to that of adult females through their first year or longer (delayed plumage maturation). The Tawny-bellied Seedeater (Sporophila hypoxantha) is a sexually dichromatic species in which, to the human eye, the juveniles look like females. We analyzed the species' stages of plumage maturation by reflectance spectrometry and a visual model of color discrimination on captive individuals of known ages. We found that males retain a plumage different from that of adult males through their first breeding season. By the time males passed the age of 1 year, their color did not differ from that of adult males in any region of the body except the crown. Spectrophotometry also revealed differences between the plumage color of juvenile males and females, and the color-discrimination model implies that the birds should be able to detect these differences. Thus juvenile males of the Tawny-bellied Seedeater acquire adult plumage after their first breeding season but are already dichromatic during the first year. How this pattern of plumage development affects the species' reproductive or other social behavior deserves further study.